Interaction of coral reef growth to sea level change within selected marine protected area of Sarangani Bay protected seascape in Mindanao, Philippines - Carisma, Hesed Jebss M. (2023.)
With rising sea level due to global warming, a major concern is whether coral reefs can keep up with sea level rise (SLR). This concern stems from the function of coral reefs in protecting the coast through its ability to attenuate waves, provide sediments to the beach and act as the host of ecological services and provide economic benefits. The potential response of a coral reef to SLR and other stressors can be inferred from its general health and the growth rates of corals therein. This information is also useful in strategizing conservation initiatives and adaptive management techniques in marine protected areas (MPAs). This study examined how well coral reefs in the Bula MPA in Sarangani Bay Protected Seascape (SBPS) can adapt to SLR by documenting its coral cover and morphology vis-a-vis the rate of relative SLR in the area. According to findings, the local sea level in the area increased by 10 mm yr⁻¹ between 2011 and 2021. For the general reef health status, the studied reef areas were in good condition dominated by massive Porites in all of the reef zones, followed by branching Acropora, columnar Pocillopora, massive Goniastrea and branching/columnar Porites. Based on the literatures, average growth rates and range are as follows: massive Porites (10 mm yr⁻¹ ; 1.9-24.99 mm yr⁻¹), branching Acropora (104 mm yr⁻¹ ; 5.9-33 mm yr⁻¹), columnar Pocillopora (31 mm yr⁻¹; 6-66.8 mm yr⁻¹), massive Goniastrea (9 mm yr⁻¹ ; 3.8-12.5 mm yr⁻¹). The majority of the local coral lifeforms might adapt to and overcome the predicted sea level increase in the coming century. Accordingly, the presence of these dominant coral lifeforms indicates that he reefs in Bula MPA are robust and resistant to current disturbances. The presence of massive Porites causes the reefs in Bula MPA to have a slightly raised crest which acts as a natural wave breaker. Due to its potential for adaptation, the massive Porites showed resilience in the face of turbidity from land-sourced sediments, and temperature changes. However, the ability of the reef to maintain its keep-up mode with SLP would rely on the survival of coral species that play a major rle in reef accretion and how the other threats t the reef's health would develop in the future. An integrated coastal management approach is imperative to mitigate various coastal and marine stressors tht will negatively act in synergy with the impact of SLR.
Special Problem (Professional Masters In Tropical Marine Ecosystem Management). -- [Miagao, Iloilo] : University of the Philippines Visayas, July 2023.
Keywords: Sarangani Bay (Mindanao, Philippines) -- Marine protected area